Legal Aid and the Future of Access to Justice - Denvir, Catrina (Bloomsbury Academic, 2023)
This open access book provides a snapshot of the state of contemporary access to justice in England and Wales. Legal aid lawyers provide a critical function in supporting individuals to address a range of problems. These are problems that commonly intersect with issues of social justice, including crime, homelessness, domestic violence, family breakdown and educational exclusion. However, the past few decades have seen a clear retreat from the tenets of the welfare state, including, as part of this, the reduced availability of legal aid. This book examines the impact of austerity and related policies on those at the coalface of the legal profession. It documents the current state of the sector as well as the social and economic factors that make working in the legal aid profession more challenging than ever before. Through data collected via the Legal Aid Census 2021, the book is underpinned by the accounts of over 1000 current and former legal aid lawyers. These accounts offer a detailed demography and insight into the financial, cultural and other pressures forcing lawyers to give up publicly funded work. This book combines a mixture of quantitative and qualitative analysis, allowing readers a broad appreciation of trends in the legal aid profession. This book will equip readers with a thorough knowledge of legal aid lawyers in England and Wales, and aims to stimulate debate as to the fate of access to justice and legal aid in the future. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0. licence on bloomsburycollections.com